Barrett's oesophagus. Issue 877 (November 1998) - Navaratnam, R. M.; Winslet, M. C.
Abstract : Barrett's oesophagus represents the replacement of stratified squamous epithelium by metaplastic columnar epithelium for 3 cm of the distal oesophagus. Gastro-oesophageal reflux, which affects 40% of the adult population, is the principal aetiological factor. This results in predominantly acid but also bile reflux (due to duodenogastrooesophageal reflux) through the lower oesophageal sphincter, transient relaxation of which accounts for the main mechanism of reflux. Conventional Barrett's oesophagus is reported in 11-13% of patients with symptomatic reflux and short segment Barrett's oesophagus (< 3.0 cm) in 18%. Approximately 50% of these patients have recognised complications on presentation, eg, carcinoma (15%). The disparity between clinical symptoms and endoscopic severity is due to reduced oesophageal mucosal sensitivity as a consequence of prolonged mucosal acid exposure. These rather alarming figures combined with the knowledge that Barrett's oesophagus is a pre-malignant condition (the diagnosis is associated with a 25-130-fold increase of malignancy) may account for the substantial increase in junctional gastrooesophageal malignancies. Symptomatic Barrett's oesophagus should be managed with full-dose proton pump inhibitors, eg, lansoprazole. Anti-reflux surgery should be reserved for the medically fit patient with recurrent symptomatic relapse in the histological absence of premalignant change. There is no evidence suggesting that surgery can be used as a prophylactic measure against malignancy. Encouraging short-term results have been obtained with photodynamic therapy in the management of high-grade dysplasia. However, columnar epithelium has been found underlying the regenerated squamous epithelium, suggesting that life-long surveillance is warranted.